The Effect of Feeding Rules Implementation on Children in Cimahi, Indonesia - Siti Zulva; Fany Haifa Latifah (Gema Lingkungan Kesehatan, 2026)
Eating difficulties are when children do not want or refuse to eat in the type or amount according to age physiologically. Several cases of difficulty eating were found that caused malnutrition in children aged 6-24 months. According to data from the Cimahi City Health Office, Cipageran has the highest number of wasting sufferers in Cimahi city as many as 117 children from 2917 targets. In general, this study aims to identify and find out the differences in the diet of children aged 6-24 months before and after applying feeding rules. This study uses a quantitative comparative method where the researcher compares 2 treatments of a variable and is quasi experimental design with a two-group pre-post-test design with the number of respondents for the intervention group of 32 respondents and the control group of 32 respondents, so the total sample is 64 respondents. In the intervention group after the post test was carried out, the child's diet increased to be appropriate with a p value of 0.0001 <0.05, while in the control group there was no change in the pre post-test with a p value of 0.199 >0.05. There was a significant difference between pre and post-test feeding rules in the intervention group while in the control group there was no significant difference. The characteristics at the age of 11-24 months are most common in women and the age of parents is most found at the age of 26-35 years. By implementing feeding rules, it is proven that it can improve children's diets with a p-value of 0.0001 <0.05. On the other hand, not applying feeding rules proves that it cannot improve the pattern of children with a p-value of 0.199 >0.05. There was a difference in dietary changes with a p value of 0.0001 <0.05.